Tragic Theoxena: Livy, Iterative History, and Performance - Haywood, Bethany (Pnyx: Journal of Classical Studies, 2025)
The Theoxena episode (Liv. 40.4) is a shining example of how Livy crafts a tragic narrative through intratextual and intertextual references. Discussed briefly by earlier scholarship, the iterative nature of the Theoxena episode has not been fully explored, especially in the context of tragedy. In this paper, I examine Theoxena’s characterization in four aspects: (1) Livy’s vocabulary throughout the episode that establishes Theoxena’s place within the family unit, and highlights the transgression associated with her actions; (2) Theoxena’s relationship with Verginius and how Livy differentitates between a noble act of sacrifice and a horrific act of murder; (3) Further intratexts with Livian episodes which deepen the connection between Theoxena and tragedy; (4) Theoxena’s relationship with Euripides’ Medeia, and how Livy uses this intertext to paint Theoxena as a murderous mother. I argue that Livy uses the performance of the tragedy genre and gender to create a tragic space in which Theoxena’s actions are portrayed not only as heinous but, more importantly, as transgressive and disruptive. In a single sentence, then, Livy uses the iterative nature of Greek tragedy to make the Theoxena episode dramatic on several levels, which rely on literary echoes of his own corpus and of Greek and Roman tragedy on the whole.